(untitled) (Damu Journal of Sport Sciences, 2025)
In order to achieve the research objectives, which are to classify and select junior players according to the most important physical, motor, and motor abilities of junior basketball players in Iraq for the 2018-2019 sports season, the researchers had to take a set of procedures and measures to identify the factors that saturated the batteries. For this purpose, the descriptive approach was used, and the research sample was defined as (90) junior basketball players representing various specialized schools. The statistical package was used. (SPSS) was used to process statistical data after conducting physical and motor tests and body measurements. Based on the results, the following conclusions were reached: 1- In light of the measurements and tests related to the physical determinants and abilities studied, junior basketball players were classified into three categories representing playing positions. 2-As a result of the factorial study of the determinants and abilities studied, three test batteries were derived, each representing a specific category of junior basketball players. 3- By applying the derived equations to the players, taking into account their results in standard scores and percentile ranks, the selection process was completed for the most outstanding players.